2020
DOI: 10.1186/s12876-020-01193-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associated factors and medication for symptoms related to gastroesophageal reflux disease among 1114 private-tuition students of Anuradhapura, Sri Lanka

Abstract: Background: Gastroesophageal reflux disease (GORD) is a chronic and a common condition worldwide which causes mild to severe symptoms. Private tuition attendees are a group which could have potential risk factors for GORD. Therefore, we aimed to determine the prevalence, associated factors and medication for symptoms related to GORD among advanced level private-tuition attendees of Anuradhapura, Sri Lanka. Methods: A descriptive cross-sectional study was conducted among students aged ≥18 years. A self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
1
11
2
Order By: Relevance
“…However, when it comes to the studies among university students, our findings were consistent with other studies were conducted in Shaqra university in 2018-2019 and King Abdulaziz University in 2019, which revealed a comparable percent of the prevalence of GERD among students (23.8%, 25.9% respectively) [11,12]. Further, our results are higher than another study in Chinese college freshmen, the prevalence was 5.1% and it is lower than the study that was conducted in 1114 private-tuition students of Anuradhapura in Sri Lanka; the prevalence was 52% [13,14]. These data suggested that GERD symptoms are a significant health problem among Saudi students.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…However, when it comes to the studies among university students, our findings were consistent with other studies were conducted in Shaqra university in 2018-2019 and King Abdulaziz University in 2019, which revealed a comparable percent of the prevalence of GERD among students (23.8%, 25.9% respectively) [11,12]. Further, our results are higher than another study in Chinese college freshmen, the prevalence was 5.1% and it is lower than the study that was conducted in 1114 private-tuition students of Anuradhapura in Sri Lanka; the prevalence was 52% [13,14]. These data suggested that GERD symptoms are a significant health problem among Saudi students.…”
Section: Discussioncontrasting
confidence: 64%
“…This is confirmed by our findings, which showed that there is a positive association between smoking and the development of reflux disease. However, other studies revealed no association between GERD and smoking [12,14]. Moreover, Khat chewing is traditionally practiced by different groups in our region, and the use of Khat chewing was a statistically significant risk factor of GERD (p<0.05).…”
Section: Discussionmentioning
confidence: 56%
“…The search strategy identified 482 citations. From these, there were 20 articles that fulfilled the eligibility criteria, representing 21,598 young school‐going participants 8,9,18–35 . Study selection procedures are illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…As GERD prevalence is rising in young populations, prevalence rate in this study is significantly lower than those reported in western countries, especially in studies conducted in 2016 and later from 25.9% to 52.1%. 9,21,30 A more precise demographic construct of GERD epidemiology in younger populations is needed because the youth are going through one of the most eventful periods of life and their lifestyles could be constantly changing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation